Gendered mediating role of substance use in the path from internet addiction or gambling to active violence in youth in the region of Mahdia, Tunisia - Mlouki, Imen; Hssan, Safa; Hariz, Emna; Ajmi Blout, Aya; Silini, Ahlem; Moustafa, Ahmed; Ben Cheikh, Mohamed Hedi; El Mhamdi, Sana (Frontiers in Psychiatry, 2025)
IntroductionThe literature shows a gap regarding mechanisms and mediators explaining the path from IA and gambling to violence. Our study aimed to investigate the gender-specific difference in the path linking IA and gambling to active violence mediated by substance use among schooled adolescents in the region of Mahdia (Tunisia).MethodsWe performed a cross-sectional survey among schooled youth in the region of Mahdia in April 2023. We conducted a mediation analysis using in SPSS the PROCESS macro to examine the relationship between X (IA/Gambling), the mediator M (Substance use), and Y (Active violence). Causal interpretations cannot be definitively established. We used validated Arabic versions of the Internet Addiction Test, the South Oaks Gambling Screen Test, the CDC Health Appraisal section about substance use and the Hospital Anxiety and Depression Scale. We also probed violence perpetration. Data analyses were performed using SPSS version 20.ResultsA total of 1594 students completed the questionnaire with a mean age of 17.75 ± 1.34 years. IA was noted in 52.3% of the participants. Gambling was more prevalent among males (12.1% vs 0.9%, p<0.001). Substance use was noted in 18.4% of participants (41.3% males vs 9.5% females, p<0.001). Violence perpetration was reported by 35.3% of the participants (59.9% males vs 25.8% females, p<0.001).After accounting for anxiety and depression, substance use mediated the link between IA and active violence (mediation%= 15.7, p< 0.001) with a higher effect in males (35.8% vs 10.5%). The mediation between gambling and violence via substance use was also significant (28.2%, p < 0.001). This effect was found only among males (27.7%).ConclusionImplementing preventive strategies and focusing on addictive behaviors such as IA, gambling and substance use is urgently needed to prevent violence perpetration among youth. However, based on our results, the cross-sectional design limits causal interpretations.